Making the weekend work: a local quality improvement project to establish and improve the quality of weekend handover. Issue 3 (25th July 2018) - Heller, Rosalie Amanda; Hu, Lisi
Abstract : Handover is widely identified by the National Confidential Enquiry into Patient Outcome and Death, the Royal College of Physicians (RCP) and Health Foundation as an area that can lead to shortcomings in patient care. We recognised that the current weekend handover process in the Trauma and Orthopaedics department at Frimley Park Hospital was dated, time-consuming and did not promote handover of sufficient patient details. The Royal College of Surgeons, British Medical Association and RCP have guidelines on handover. Our aim was to use these to establish the quality of handovers and introduce methods to better the accuracy and effectiveness of weekend handover in the department, thus improving patient care and safety. Initially, we measured the quality of the existing handover documentation for how comprehensively it was completed. We then implemented a two-step change, reauditing each step, resulting in a handover tool on the trust intranet. Finally, we repeated our audit to monitor sustainability. The 10 categories measured were: 'Patient name', 'Date of birth', 'Hospital number', 'Date of admission', 'Location', 'Consultant', 'Admission reason', 'Date of operation', 'Frequency of review' and discharge paperwork ('TTO'). The original handover documentation had good compliance with 'Patient name' (99%), 'Hospital number' (94%) and 'Admission reason' (91%) but was poor in all other categories, ranging from 12% to 84%. The only category that met its standard was 'Admission reason'. Almost every category improved with the new intranet tool. Five areas met their standard ('Patient name', 'Location', 'Consultant', 'Admission reason' and 'Frequency of review'). Specific prompts resulted in 100% compliance for 'Frequency of review'. The poorest compliance was again seen for 'TTO' (18%). In a short four months, we created an intranet handover tool that resulted in significant and sustainable improvements in the quality, detail and accuracy of handovers, making identification of sick patients safer and more efficient.